La Ville, Le Jardin, La Mémoire. - Abramović, Marina; Akita, Masami; Arienti, Stefano; Bawa, Geoffrey; Bossé, Laurence; Brunon, Hervé; Cherubini, Laura; Christov-Bakargiev, Carolyn; Clément, Gilles; Di Pietrantonio, Giacinto; Durham, Jimmie; Gioni, Massimiliano; et al. (Rome : Académie de France à Rome - Villa Médicis, 2000)
Aballéa, Martine ; Abramovic, Marina ; Acconci, Vito ; Benin ; Akita Masami ; Almarcegui, Lara ; Althamer, Pawel ; Alves, Maria Thereza ; Amer, Ghada ; André, Mark ; Anselmo, Giovanni ; Arienti, Stefano ; Armleder, John M. ; Arpiani, Pagliarini ; Arroyo, Pedro ; Asdam, Knut ; Atelier Alias ; Atelier Feichang Jianzhu ; Bagnoli, Marco ; Balkin, Amy ; Baltzer, Bruno ; Banz, Stefan ; Bartolini, Massimo ; Baruchello, Gianfranco ; Basilico, Gabriele ; Bawa, Geoffrey ; Behnish & Partner ; Bei, Neda ; Bello, Paola Di ; Benson, Jane ; Berger, Laurent P. ; Blazy, Michel ; Bodzianowski, Cezary ; Boeri, Stefano ; Bossé, Laurence ; Bovier, Lionel ; Boyadjiev, Luchezar ; Braine, Bob ; Brunon, Hervé ; Bucher, Anne-Marie ; Buckingham, Matthew ; Bul, Lee ; Bunschoten, Raoul ; Burckhardt, Lucius ; Buren, Daniel ; Cai Guo-Qiang ; Cardiff, Janet ; Cattelan, Maurizio ; Chang Yung Ho ; Chen Zhen ; Choochuey, Rachaporn ; CJ Lim ; Clément, Gilles ; CLIOSTRAAT ; Cresci, Fabio ; Critical Art Ensemble ; Cucchi, Enzo ; D'Heilly, David ; Décosterd & Rahm ; Denis, Marie ; Dion, Mark ; Doderer, Yvonne P. ; Dopopaesaggio ; Dunne, Anthony ; Durham, Jimmie ; Eichhorn, Maria ; El-Hassan, Róza ; Etkin, Suzan ; Evans, Cerith Wyn ; Fagen, Graham ; Fanderl, Helga ; Fernández, Teresita ; Filomeno, Angelo ; Fischli, Peter ; Fleury, Sylvie ; Fontaine, Thierry ; Framis, Alicia ; Friedmann, Gloria ; Gabor, Rosko ; Gadea, Ernesto ; Galantai, Gyorgy ; Galbiati, Alessandra ; Gautel, Jakob ; Gerhes, Gábor ; Gilbert & George ; Gill, Simryn ; Gilsoul, Nicolas ; Ginsburg, Hope ; Gioni, Massimiliano ; Goldberg, Ken ; Graham, Dan ; Graziani, Bruno ; Grill 5 ; Gruppo A 12 ; Guk ; Hadid, Zaha ; Hallsson, Hlynur ; Hanimann, Alex ; Hapaska, Siobhán ; Hastenteufel, Sandra ; Hayes, Paula ; Heinecke, Katja ; etc.
Italiaans & Engels & Frans
La Ville, Le Jardin et La Mémoire, Académie de France à Rome - Villa Médicis, Roma, 21.06.2000 - 24.09.2000
boek